Capacitive biosensor for detection of histamine. - Salleh, Abu Bakar; Abu Bakar, Fatimah; Lee, Yook Heng; Wagiran, Rahman; Wasoh @ Mohamad Isa, Helmi (2008)
Biosensor is made using an enzyme diamine oxide (DAO) and a capacitance (C) concept. It give linear range of histamine from 25 to 100ppm and the responce time is 2 minutes which is considerably fast to detect histamine in food.